THE IMPACT OF FINANCIAL LEARNING ON INTERNATIONAL PORTFOLIOS-AN APPLIED STUDY FOR A NUMBER OF ECONOMIES - Hebat Allah Mustafa; Hayder M. Kareem Alduhaidahawi; Mustafa S. Abdulreza (American Journals, 2023)
This study aims to highlight the role and importance of financial education and its impact on international portfolios for a number of economies and its role among financial portfolios, as the ability of individuals Determined through the use of basic financial and economic concepts , which play an important role in achieving an appropriate level of financial well - being. learning financial in education Knowledge and skills and behaviors necessary to adopt management practices money in order to gain profits and savings and borrow And investment , as the study conducted a detailed analysis of the economies’ portfolios during the period (2005-2020 ) and in light of the data obtained for the study sample represented in the portfolios of foreign and local stocks and the market values of those portfolios as well as several other determinants, and the study sample consisted of ( 64 ) A foreign portfolio , and using many financial and statistical methods, the study reached many conclusions and recommendations, the most important of which are : It is noted that there is a disparity among emerging economies that tend to benefit more from the improvement in the level of financial education compared to their developed counterparts, in addition to the fact that the positive impact of financial education was more evident during the recent financial crisis, especially for economies with less developed financial markets. The study concluded in the most important recommendation: it should Enhancing the level of efficiency of investors and encouraging them to diversify their investment portfolios in terms of foreign investments, as it will help raise the level of financial education and reduce the country's bias towards local equities In order to take advantage of external opportunities to achieve the best trade-off between efficiency for return and risk.
Keywords: Financial education; country bias; stock markets.